Preliminary Design Of Titanium Dioxide From Ilmenite Capacity Of 50,000 Tons/Year - Rendra, Yulira Kus; , Dr. Ir. H. Ahmad. M. Fuadi, M.T; , Ir. Nur Hidayati, M.T,.Ph.D (2017)
Titanium dioxide is mostly used by the chemical industry as a pigment for the production of fiber, paint, cosmetics, and polymers. Titanium dioxide plant was designed with a capacity of 50,000 tons/year. Titanium dioxide plant is planned to be built in 2020 on the island of Bangka Belitung. Plant location is close to ilmenite as raw material sources. Marketing of titanium dioxide is to meet domestic demand By reacting ilmenite with chlorine (Cl2) to produce titanium tetrachloride (TiCl4), using coke as a reducing agent in a fluidized bed reactor. reactor operated continuously at 900 ℃ and 1 atm pressure. Furthermore, the output of reactor 1 will be purified before passing it to the reactor 2, with the type of fluidized bed reactor that operates continuously at temperatures of 1000 ℃ and 1 atm pressure. In reactor 2, the reaction between titanium tetrachloride (TiCl4) and hot air will produce titanium dioxide and chlorine gas, then the chlorine (Cl2) will recycle back to the reactor 1. The production of titanium dioxide as much as 50,000 tons/year, requires raw materials ilmenite as much 18314.8573 kg/h, chlorine gas as much 27472.2860 kg/h and cokes as much 4578.7143 kg/h, as well as byproducts produced in the form of iron (III) chloride (FeCl3) as 16555.6602 kg/h. For process water, obtained from Manggar river as much as 29.9064 m3/h, electricity needs as much 639.7765 Kw, and fuel oil 2394.8983 L/h. The results of economic analysis of preliminary design of titanium dioxide plant obtained that the fixed capital of 617,308,652,185.6490 IDR; Working capital amounted to 317,932,683,253.9200 IDR; and total product cost 2,032,787,067,878.7600 IDR. from feasibility analysis results obtained ROI before tax 69.1261% and after-tax 49.3404%. POT before tax 1.2638 years and after tax 1.6852 years, BEP 44.6073%; SDP 33.1827%. and IRR 56.8817%.